Performance Enhancement of Mixing Impellers Based on Mixture PPM Analysis - Pratama, Aditya Tirta; Zuardi, Gunawan (Green Engineering Society, 2025)
Achieving optimal fertilizer mixing is crucial for farmers, as it directly affects product quality, homogeneity, and overall production efficiency. However, the exact degree of mixing uniformity remains uncertain due to the lack of TDS meters or sensors in the field. This research aims to compare the performance of a novel paddle and PBT-4 impeller while generating empirical data that can serve as a reference for mixing NPK fertilizers. The findings will help farmers to determine the appropriate mixer and optimal mixing duration. The Define-Measure-Analyze-Improve-Control (DMAIC) approach was employed to develop and implement the proposed mixing impellers. Comparative analysis indicates that the novel paddle outperforms the PBT-4 impeller in mixture homogeneity, as evidenced by its lower Coefficient of Variation (COV) of 0.00163 compared to 0.0229. No significant difference was observed in the time required to reach steady ppm or settling time. Ppm is a crucial parameter for assessing mixing uniformity and product quality. While both the Paddle and 4-blade PBT exhibited similar mixing times, the Paddle demonstrated slightly superior performance in achieving uniformity.